Effects of Centella asiatica L. On Spatial Memory and Bcl-2 Gene Expression in the Hippocampus of Rats Injected With Trimethyltin - Sapto Yuliani; Muhammad Faishal Akbar; Nurfidho Rochmafihro; Yosi Uthary; Lasmi Deslaila (Indonesian Journal of Pharmacy, 2021)
Cell death (apoptosis) in the hippocampus is related to impaired memory functions. Gotu kola (Centella asiatica) contains asiatic acid and asiaticoside, which act as antioxidants and improve memory function. This study was intended to determine the effects of gotu kola extracts on Bcl-2 gene expression and spatial memory in rats with impaired memory functions due to trimethyltin (TMT) injection. The rats were subdivided into six groups, each group consisting of 10. The normal group was given sodium carboxymethyl cellulose (CMC-Na); the TMT group was given CMC-Na; the positive group was given 200 mg/kg bw citicoline; the extract groups were given a variation of gotu kola extract at 100 (P100), 200 (P200), and 400 mg/kg bw (P400) doses, respectively. These treatments were conducted for 35 days. TMT was injected intraperitoneally on Day 8 of treatment at a dose of 8 mg/kg bw in all groups except the normal group. On Days 29-35, the Morris water maze (MWM) spatial memory test was conducted. The rats were sacrificed, and their hippocampi were taken for immunohistochemical observation of Bcl-2 gene expression. The results showed TMT injection could lower the spatial memory of rats in the MWM and cause apoptosis of the pyramidal cells of the hippocampus. Gotu kola extract at 100, 200 and 400 mg/kg bw could increase the percentage of time spent (duration) and frequency of rats staying in the target quadrant in the probe trial of the MWM and increase Bcl-2 gene expression in the pyramidal cells of the hippocampus. Overall, the results have confirmed that gotu kola extract has the potential to prevent hippocampal cell death and improve the spatial memory of rats injected by TMT.